Non-probabilistic method to consider uncertainties in frequency response function for vibration-based damage detection using artificial neural network - Khairul Hazman Padil, 1990-, author 546295; Norhisham Bakhary supervisor 559744; Fakulti Kejuruteraan. Sekolah Kejuruteraan Awam 619085 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2020)
Thesis (Ph.D (Kejuruteraan Awam)) - Universiti Teknologi Malaysia, 2020